Knowledge of Dietary Recommendations, Food Availability, and Food Selection Attitudes of Adults during the COVID-19 Pandemic - Elvira Dona Lukmana; Meirina Dwi Larasati; Mohammad Jaelani (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2023)
SARS-CoV-2, the novel coronavirus responsible for COVID-19 disease, has affected all regions of Indonesia, leading to an increase in cases and prompting the Indonesian government to impose Large-Scale Social Restrictions (LSSR). Prolonged exposure to LSSR can potentially impact diet, dietary availability, and food preferences. Therefore, understanding the knowledge of dietary recommendations during the COVID-19 pandemic is crucial to support individuals in maintaining a healthy diet and lifestyle. This study aims to investigate the relationship between knowledge of dietary intake recommendations, food availability, and food selection attitudes among adults during the COVID-19 pandemic. A cross-sectional design was employed, and 124 individuals were selected as research subjects using a purposive sampling technique. The data on knowledge, food availability, and attitudes towards food selection were collected through a Google Forms questionnaire. Statistical test was conducted using the Fisher Exact test to determine the relationship between variables. The findings of this study demonstrated no correlation between knowledge and food selection attitude (p>0.05), as well as between food availability and food selection attitude (p>0.05). However, there was a tendency for individuals with good knowledge to have good attitudes and individuals with good attitudes to have sufficient food availability, despite the absence of statistical correlation.